Double cross-linked graphene oxide hydrogel for promoting healing of diabetic ulcers - Liu, Wenxu; Yang, Yunfang; Li, Meiying; Mo, Jingxin (Frontiers in Chemistry, 2024)
This study explores the synthesis and characterization of a novel double cross-linked hydrogel composed of polyvinyl alcohol (PVA), sodium alginate (SA), graphene oxide (GO), and glutathione (GSH), henceforth referred to as PVA/SA/GO/GSH. This innovative hydrogel system incorporates two distinct types of cross-linking networks and is meticulously engineered to exhibit sensitivity to high glucose and/or reactive oxygen species (ROS) environments. A sequential approach was adopted in the hydrogel formation. The initial phase involved the absorption of GSH onto GO, which was subsequently functionalized with boric acid and polyethylene glycol derivatives via a bio-orthogonal click reaction. This stage constituted the formation of the first chemically cross-linked network. Subsequently, freeze-thaw cycles were utilized to induce a secondary cross-linking process involving PVA and SA, thereby forming the second physically cross-linked network. The resultant PVA/SA/GO/GSH hydrogel retained the advantageous hydrogel properties such as superior water retention capacity and elasticity, and additionally exhibited the ability to responsively release GSH under changes in glucose concentration and/or ROS levels. This feature finds particular relevance in the therapeutic management of diabetic ulcers. Preliminary in vitro evaluation affirmed the hydrogel's biocompatibility and its potential to promote cell migration, inhibit apoptosis, and exhibit antibacterial properties. Further in vivo studies demonstrated that the PVA/SA/GO/GSH hydrogel could facilitate the healing of diabetic ulcer sites by mitigating oxidative stress and regulating glucose levels. Thus, the developed PVA/SA/GO/GSH hydrogel emerges as a promising candidate for diabetic ulcer treatment, owing to its specific bio-responsive traits and therapeutic efficacy.